Physiological Response of Bligon Buck to Transportation: Relation to Level of Thyroid Hormone - Astuti, Pudji; -, Sarmin; Kusumawati, Asmarani; Mona Airin, Claude; Maheshwari, Hera; Sjahfirdi, Luthfiralda (Jurnal Veteriner, 2010)
Transportated animals may subject to a variety of physical stimuli including metabolism, crowding,noise, handling, isolation, agitation, and extreme temperature .The aim of this study was to determine thechanges of serum T4 and T3 concentration, during animals transportation. Six adult Bligon buck with bodyweight ranging from 26-30 Kg were used in this study. Two weeks prior to the experiment, the animalswere given anthelmintic Albendazole to eliminate egg worm. All animals were fed standard diet in theirpen at 10% of their body weight per head daily and commercial concentrate also given everyday. Freshwater was provided ad libitum. All animals were transported around village for 16 hours starting from18.00 pm until 10.00 am in open small truck (3 x 2 m); eye contact each others would be possible. Bloodsamples were withdrawn from jugular vein using vacutainer tubes containing heparin into 1.5 mL glasstubes, then centrifuged at 500 g for 15 minutes. Plasma was collected to be stored at –20° C. The bloodwere collected every 4 hours from 8 hours before transportation ( at 10.00 am, 14.00 pm and 18.00 pm)until the time of arriving after transportation at 10.00 am. Plasma was harvested and stored at –20° Cuntil T3 and T4 concentrations were measured using ELISA method (enzyme linked immunosorbentassay) product DRG, Germany. The result showed that transportation of Bligon bucks for 16 hours havean affect on level of T4 only (P<0.05) and not for T3 concentration (P>0.05) due to physical stimuli such ascrowding, heat stress, noise, handling would be discarded so that the metabolic process was stable. Duringtransportation, decreasing of T4 levels indicated conversion of T4 to T3 to form active hormone.
Keywords: Bligon bucks, transportation, Triiodothyronine (T3), Thyroxine (T4)